"Little Goodies in His Kit Bag": British Servicemen, Masculinity, and Feeding the Home Front in World War II. Issue 3 (2nd September 2021) - Spring, Kelly A.
ABSTRACT: In World War II, the British government called on all able-bodied men to join the forces and defend the country, enabling them to fulfill the role of ideal male in wartime. These men also performed masculinity by provisioning families with gifts of food from their service abroad. Such food added to the overall caloric levels of a population on rations, offered a material form of comfort, and sustained connections between the military and home fronts. This article utilizes written memoirs from the BBC's WW2 People's War website to examine people's memories of servicemen's work with food. These remembrances illuminate the diverse ways in which men, serving in all branches of the forces (Army, RAF, Navy, and Merchant Navy), helped to support the nutrition and well-being (physical and emotional) of British families. Through the lens of food, this article offers a complex and multifaceted view of wartime masculinity.